Cardiac 123I-mIBG Imaging in Heart Failure - Derk O. Verschure; Kenichi Nakajima; Hein J. Verberne (MDPI AG, 2022)
Cardiac sympathetic upregulation is one of the neurohormonal compensation mechanisms that play an important role in the pathogenesis of chronic heart failure (CHF). In the past decades, cardiac 123I-mIBG scintigraphy has been established as a feasible technique to evaluate the global and regional cardiac sympathetic innervation. Although cardiac 123I-mIBG imaging has been studied in many cardiac and neurological diseases, it has extensively been studied in ischemic and non-ischemic CHF. Therefore, this review will focus on the role of 123I-mIBG imaging in CHF. This non-invasive, widely available technique has been established to evaluate the prognosis in CHF. Standardization, especially among various combinations of gamma camera and collimator, is important for identifying appropriate thresholds for adequate risk stratification. Interestingly, in contrast to the linear relationship between 123I-mIBG-derived parameters and overall prognosis, there seems to be a "bell-shape" curve for 123I-mIBG-derived parameters in relation to ventricular arrhythmia or appropriate implantable cardioverter defibrillator (ICD) therapy in patients with ischemic CHF. In addition, there is a potential clinical role for cardiac 123I-mIBG imaging in optimizing patient selection for implantation of expensive devices such as ICD and cardiac resynchronization therapy (CRT). Based on cardiac 123I-mIBG data risk models and machine learning, models have been developed for appropriate risk assessment in CHF.